A Case Report on Fever of Unknown Origin in a School Going Child– An Uncommon Answer in a Common Question - Shrestha, Dhan Bahadur; Mool, Suju; Karki, Sijan (Medical Journal of Shree Birendra Hospital, 2018)
Fever is one of the commonest complaints in paediatrics outpatient as well as inpatient department. Fever of unknown origin (FUO) is a diagnosis of exclusion given to the febrile condition lasting more than three weeks with temperature 38.30C or more with unknown cause despite of one week in patient care. Here we present a case of FUO in a child which was investigated thoroughly and managed on the line of enteric fever. However, the patient remained febrile. Hence, further investigations were undertaken and finally, bone marrow culture grew a very uncommon organism- Escherichia coli. The child was treated as per the sensitivity and responded well to treatment and was discharged after improvement. Here, we would like to present this case of FUO to highlight the possibility of bone marrow invasion by an uncommon organism as a source of fever in children.